2012
DOI: 10.1186/1471-2407-12-28
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of STAT3 signaling and induction of SHP1 mediate antiangiogenic and antitumor activities of ergosterol peroxide in U266 multiple myeloma cells

Abstract: BackgroundErgosterol peroxide (EP) derived from edible mushroom has been shown to exert anti-tumor activity in several cancer cells. In the present study, anti-angiogenic activity of EP was investigated with the underlying molecular mechanisms in human multiple myeloma U266 cells.ResultsDespite weak cytotoxicity against U266 cells, EP suppressed phosphorylation, DNA binding activity and nuclear translocalization of signal transducer and activator of transcription 3 (STAT3) in U266 cells at nontoxic concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…Natural cell growth and death were modeled using first-order growth rate constants (k g and k d ). The estimated net growth rate constant (k g -k d ) in the final model (0.00490 h 21 ) is comparable to net growth rate constants from U266 xenografts at 0.00487 h 21 (Siveen et al, 2014) and 0.00450 h 21 (Rhee et al, 2012) that were obtained by fitting an exponential model to digitized control curves (data not shown).…”
Section: Discussionmentioning
confidence: 75%
“…Natural cell growth and death were modeled using first-order growth rate constants (k g and k d ). The estimated net growth rate constant (k g -k d ) in the final model (0.00490 h 21 ) is comparable to net growth rate constants from U266 xenografts at 0.00487 h 21 (Siveen et al, 2014) and 0.00450 h 21 (Rhee et al, 2012) that were obtained by fitting an exponential model to digitized control curves (data not shown).…”
Section: Discussionmentioning
confidence: 75%
“…In a number of cases their chemical synthesis appears more convenient, especially if the initial ∆ 5,7 -or ∆ 5,7,9(11) -sterols are available. This is also favored by the circumstance that chemical synthesis of 5,8-epidioxides are based on the well-studied photochemical oxidation of 5,7-diene group in sterols (Figure 10).…”
Section: Synthesismentioning
confidence: 99%
“…In ethanol, the expected 1 and main products (22E)-ergosta-5,7,9,22-tetraen-3β-ol (DHE) and by-product (22E)-5α,8α-epidioxyergosta-6,9,22-trien-3β-ol (EEP9 (11)), (22E)-ergosta-6,9,22-triene-3β,5α,8α-triol (DHOE) were obtained. In methyl tert-butyl ether, a complex mixture of 1, KE, DHOE, EEP9 (11) In cases where the initial ∆ 5,7 -sterols are unavailable, special schemes of synthesis must be developed for obtaining the 5,8-epidioxides. The synthesis of endoperoxide 3 started from cholesterol, cholesterol was converted to cholesterol-3-acetate to protect the hydroxy group [40].…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the most aggressive human cancers, the 5-year survival rate of pancreatic ductal adenocarcinoma (PDAC) is <5% (1). Recent studies suggested that bioactive compounds from mushrooms could protect against multiple myeloma, breast and skin cancer (2)(3)(4)(5). Poria cocos (also known as Wolfiporia extensa) is a medicinal mushroom in the Polyporaceae family that grows in pine trees and its sclerotium is widely used in traditional Asian medicine for its sedative, diuretic, digestive and tonic effects (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%